2006
DOI: 10.1152/ajprenal.00229.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of lymphocytes from mice with renal ischemia can induce albuminuria in naive mice: a possible mechanism linking early injury and progressive renal disease?

Abstract: Severe ischemia-reperfusion injury (IRI) predisposes to long-term impairment in kidney function both in patients and experimentally through unknown mechanisms. Given emerging evidence implicating lymphocytes in the pathogenesis of early injury to kidney, liver, and lung after IRI, we hypothesized that kidney IRI would potentially release or expose normally sequestered antigens that would lead to proliferation of antigen-recognizing lymphocytes. This, in turn, would directly participate in progressive kidney in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 25 publications
3
37
1
1
Order By: Relevance
“…Ischemia and/or reperfusion initiates changes in vascular endothelial cells, tubular epithelial cells, and leukocytes that result in the loss of immune system homeostasis in the kidney with a consequent inflammatory response (16). Animal studies have demonstrated that AKI causes permanent damage to the microvasculature with subsequent abnormalities in kidney structure and function (17). Basile et al (18) demonstrated that recovery from ischemia-reperfusion injury in rats is not complete and that it compromises sodium hemostasis and predisposes to hypertension and secondary renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia and/or reperfusion initiates changes in vascular endothelial cells, tubular epithelial cells, and leukocytes that result in the loss of immune system homeostasis in the kidney with a consequent inflammatory response (16). Animal studies have demonstrated that AKI causes permanent damage to the microvasculature with subsequent abnormalities in kidney structure and function (17). Basile et al (18) demonstrated that recovery from ischemia-reperfusion injury in rats is not complete and that it compromises sodium hemostasis and predisposes to hypertension and secondary renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Rat leukocytes have been found to secrete angiotensinogen (35), human neutrophils and mast cells were shown to convert AngI to AngII (36), and binding sites were found on human mononuclear cells by using radioactively labeled AngII (37). Although the contribution of monocyte-derived macrophages is established in the pathogenesis of kidney and vascular lesions, other leukocytes, such as NK cells, T cells, and DC, are shown to play crucial roles in renal and vascular diseases (16,38,39). AngII was previously shown to augment murine splenic lymphocyte proliferation by Nataraj et al (40) and others (41), and angiotensin receptor blockers suppress murine T cell antigen responses (42).…”
Section: Discussionmentioning
confidence: 99%
“…Increased IFN-γ production was not only found in ischemic organs, but also in splenic T cells in the late phase of severe renal IRI without any change in CD4 + and CD8 + T cells numbers [41]. Adoptive transfer of splenic lymphocytes from mice with severe renal IRI induced albuminuria in naïve mice accompanied by migration of donor lymphocytes to recipient kidney and increase of activated and memory T cells in recipient spleen [53]. CD4 + T cells deficient in CD28 or IFN-γ did not restore ischemic injury in nu/nu mice, CD4 KO mice or RAG1 KO mice [40].…”
Section: Different Roles Of T Cell Subsets In Irimentioning
confidence: 93%